The Relationship of Traders' Participation, the Role of Managers, and Policies with Waste Management - Yuniati, Yuniati; Januariana, Neni Ekowati; Syafitri, Ramadhani (Journal of Midwifery and Nursing, 2024)
Waste is something that is not used, is not worn, is not liked, or is something that is thrown away that comes from human activities and does not happen by itself. Based on a survey conducted by researchers at Pancur Batu Market, Deli Serdang Regency, traders do not participate enough in waste management, traders still throw waste carelessly and do not collect and separate waste according to type, and there is a lack of information provided by market managers regarding market management policies. This research aims to determine the relationship between trader participation, the role of managers and policies in waste management at Pancur Batu Market, Deli Serdang Regency. This type of research is quantitative research with a cross sectional design. The population of this research was 600 traders at Pancur Batu Market, Deli Serdang Regency. The research sample was 86 traders using proportional random sampling techniques. Data were analyzed univariately and bivariately using the chi-square test. The results of this study indicate that trader participation has value (p = 0.024 < 0.05), the role of managers (p = 0.030 < 0.05), and policy (p = 0.000 < 0.05) with waste management at the Pancur Batu Regency Market Deli Serdang in 2024 It is recommended that the Pancur Batu market management provide information regarding waste management policies and provide strict sanctions if traders throw rubbish carelessly.